[2+2] Photochemical Cycloaddition in Organic Synthesis. Issue 10 (3rd December 2019) - Sarkar, Debayan; Bera, Nabakumar; Ghosh, Subrata
Abstract : The century old [2+2] photocycloaddition reaction appeared as the most synthetically useful reaction amongst all photochemical reactions. It provides not only cyclobutane ring systems, but at the same time it provides access to medium rings through facile ring expansion/fragmentation of the strained cyclobutane ring. The high regio‐and stereoselectivity observed during cycloaddition has made it an attractive tool for synthesis of multicyclic structurally complex natural products. The vast majority of [2+2] photocycloaddition reactions involves enone–alkene cycloaddition which is conveniently achieved through direct excitation or sensitization by UV irradiation. Substantial progress has also been made in [2+2] cycloaddition between two unactivated alkenes using transition metal salts especially copper(I) salts. Sometimes Cu(I)‐catalyzed cycloaddition is advantageous over enone–alkene photocycloaddition. Search for an alternative source to environmentally harmful high energy UV light has led to the discovery of transition metal salts which can be used to excite alkenes by visible light. This causes alkenes to undergo [2+2] cycloaddition and has been used for synthesis of cyclobutane derivatives. This review aims to give an overview about different aspects of [2+2] photocycloaddition reaction with an emphasis in the stereoselective synthesis of selected complex natural products and related molecules where cycloaddition has been used as the key step. Abstract : This account gives an overview of [2+2] photocycloaddition involving inter‐ and intramolecular enone–alkene cycloaddition through direct or sensitized irradiation, Cu(I)‐catalyzed alkene–alkene cycloaddition, and more recently developed photoredox catalysis to make cyclobutane derivatives. Emphasis has been given to application of these processes in the total synthesis of cyclobutane containing natural products and related structures. This has been highlighted with selected examples of synthesis of natural products.